I have 2 groups of people. I'm working with the data about their age. I know the means, the standard deviations and the number of people. I don't know the data of each person in the groups.

Group 1 :

Mean = 35 years old; SD = 14; n = 137 people

Group 2 :

Mean = 31 years old; SD = 11; n = 112 people

I want to combine those 2 groups to obtain a new mean and SD. It's easy for the mean, but is it possible for the SD? I do not know the distribution of those samples, and I can't assume those are normal distributions. Is there a formula for distributions that aren't necessarily normal?

  • $\begingroup$ Hey, welcome to Math Stackexchange! If you can, can you please add some context to the question? I'm not a stats guy but I'm a little confused by what you mean by "subjects". Thanks! $\endgroup$ – SalmonKiller Oct 25 '18 at 21:33
  • 1
    $\begingroup$ I just edited my post to add more context and be more specific. Thanks! $\endgroup$ – Nicolas Melançon Oct 25 '18 at 21:37

Continuing on from BruceET's explanation, note that if we are computing the unbiased estimator of the standard deviation of each sample, namely $$s = \sqrt{\frac{1}{n-1} \sum_{i=1}^n (x_i - \bar x)^2},$$ and this is what is provided, then note that for samples $\boldsymbol x = (x_1, \ldots, x_n)$, $\boldsymbol y = (y_1, \ldots, y_m)$, let $\boldsymbol z = (x_1, \ldots, x_n, y_1, \ldots, y_m)$ be the combined sample, hence the combined sample mean is $$\bar z = \frac{1}{n+m} \left( \sum_{i=1}^n x_i + \sum_{j=1}^m y_i \right) = \frac{n \bar x + m \bar y}{n+m}.$$ Consequently, the combined sample variance is $$s_z^2 = \frac{1}{n+m-1} \left( \sum_{i=1}^n (x_i - \bar z)^2 + \sum_{j=1}^m (y_i - \bar z)^2 \right),$$ where it is important to note that the combined mean is used. In order to have any hope of expressing this in terms of $s_x^2$ and $s_y^2$, we clearly need to decompose the sums of squares; for instance, $$(x_i - \bar z)^2 = (x_i - \bar x + \bar x - \bar z)^2 = (x_i - \bar x)^2 + 2(x_i - \bar x)(\bar x - \bar z) + (\bar x - \bar z)^2,$$ thus $$\sum_{i=1}^n (x_i - \bar z)^2 = (n-1)s_x^2 + 2(\bar x - \bar z)\sum_{i=1}^n (x_i - \bar x) + n(\bar x - \bar z)^2.$$ But the middle term vanishes, so this gives $$s_z^2 = \frac{(n-1)s_x^2 + n(\bar x - \bar z)^2 + (m-1)s_y^2 + m(\bar y - \bar z)^2}{n+m-1}.$$ Upon simplification, we find $$n(\bar x - \bar z)^2 + m(\bar y - \bar z)^2 = \frac{mn(\bar x - \bar y)^2}{m + n},$$ so the formula becomes $$s_z^2 = \frac{(n-1) s_x^2 + (m-1) s_y^2}{n+m-1} + \frac{nm(\bar x - \bar y)^2}{(n+m)(n+m-1)}.$$ This second term is the required correction factor.

  • $\begingroup$ Just to tie things together, I tried your formula with my fake data and got a perfect match: ((n1-1)*var(x1) + (n2-1)*var(x2))/(n1+n2-1) + ((n1*n2)*(mean(x1)-mean(x2))^2)/((n1+n2)*(n1+n2-1)) returns 1157.706 and so does var(x). Thanks, I haven't seen this formula before. $\endgroup$ – BruceET Oct 26 '18 at 2:28

Neither the suggestion in a previous (now deleted) Answer nor the suggestion in the following Comment is correct for the sample standard deviation of the combined sample.

Known data for reference.: First, it is helpful to have actual data at hand to verify results, so I simulated samples of sizes $n_1 = 137$ and $n_2 = 112$ that are roughly the same as the ones in the question.

Combined sample mean: You say 'the mean is easy' so let's look at that first. The sample mean $\bar X_c$ of the combined sample can be expressed in terms of the means $\bar X_1$ and $\bar X_2$ of the first and second samples, respectively, as follows. Let $n_c = n_1 + n_2$ be the sample size of the combined sample, and let the notation using brackets in subscripts denote the indices of the respective samples.

$$ \bar X_c = \frac{\sum_{[c]} X_i}{n} = \frac{\sum_{[1]} X_i + \sum_{[2]} X_i}{n_1 + n_1} = \frac{n_1\bar X_1 + n_2\bar X_2}{n_1+n_2}.$$

Let's verify that much in R, using my simulated dataset (for now, ignore the standard deviations):

set.seed(2025); n1 = 137; n2 = 112  
x1 = rnorm(n1, 35, 45);  x2 = rnorm(n2, 31, 11)
x = c(x1,x2)              # combined dataset
mean(x1); sd(x1)
[1] 31.19363              # sample mean of sample 1
[1] 44.96014
mean(x2); sd(x2)
[1] 31.57042              # sample mean of sample 2
[1] 10.47946
mean(x); sd(x)
[1] 31.36311              # sample mean of combined sample
[1] 34.02507
(n1*mean(x1)+n2*mean(x2))/(n1+n2)  # displayed formula above
[1] 31.36311              # matches mean of comb samp

Suggested formulas give incorrect combined SD: Here is a demonstration that neither of the proposed formulas finds $S_c = 34.025$ the combined sample:

According to the first formula $S_a = \sqrt{S_1^2 + S_2^2} = 46.165 \ne 34.025.$ One reason this formula is wrong is that it does not take account of the different sample sizes $n_1$ and $n_2.$

According to the second formula we have $S_b = \sqrt{(n_1-1)S_1^2 + (n_2 -1)S_2^2} = 535.82 \ne 34.025.$

To be fair, the formula $S_b^\prime= \sqrt{\frac{(n_1-1)S_1^2 + (n_2 -1)S_2^2}{n_1 + n_2 - 2}} = 34.093 \ne 34.029$ is more reasonable. This is the formula for the 'pooled standard deviation' in a pooled 2-sample t test. If we may have two samples from populations with different means, this is a reasonable estimate of the (assumed) common population standard deviation $\sigma$ of the two samples. However, it is not a correct formula for the standard deviation $S_c$ of the combined sample.

sd.a = sqrt(sd(x1)^2 + sd(x2)^2);  sd.a
[1] 46.16528
sd.b = sqrt((n1-1)*sd(x1)^2 + (n2-1)*sd(x2)^2);  sd.b
[1] 535.8193
sd.b1 = sqrt(((n1-1)*sd(x1)^2 + (n2-1)*sd(x2)^2)/(n1+n2-2))
[1] 34.09336

Method for correct combined SD: It is possible to find $S_c$ from $n_1, n_2, \bar X_1, \bar X_2, S_1,$ and $S_2.$ I will give an indication how this can be done. For now, let's look at sample variances in order to avoid square root signs.

$$S_c^2 = \frac{\sum_{[c]}(X_i - \bar X_c)^2}{n_c - 1} = \frac{\sum_{[c]} X_i^2 - n\bar X_c^2}{n_c - 1}$$

We have everything we need on the right-hand side except for $\sum_{[c]} X_i^2 = \sum_{[1]} X_i^2 + \sum_{[2]} X_i^2.$ The two terms in this sum can be obtained for $i = 1,2$ from $n_i, \bar X_i$ and $S_c^2$ by solving for $\sum_{[i]} X_i^2$ in a formula analogous to the last displayed equation. [In the code below we abbreviate this sum as $Q_c = \sum_{[c]} X_i^2 = Q_1 + Q_2.$]

Although somewhat messy, this process of obtaining combined sample variances (and thus combined sample SDs) is used in many statistical programs, especially when updating archival information with a subsequent sample.

Numerical verification of correct method: The code below verifies that the this formula gives $S_c = 34.02507,$ which is the result we obtained above, directly from the combined sample.

q1 = (n1-1)*var(x1) + n1*mean(x1)^2; q1
[1] 408219.2 
q2 = (n2-1)*var(x2) + n2*mean(x2)^2; q1
[1] 123819.4
qc = q1 + q2
sc = sqrt( (qc - (n1+n2)*mean(x)^2)/(n1+n2-1) ); sc
[1] 34.02507
  • $\begingroup$ This page also shows this method getting the variance of a combined sample. $\endgroup$ – BruceET Oct 26 '18 at 2:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.